Description of a new species of Prolixus (Acari: Trombidiformes: Tenuipalpidae) from Austroderia splendens (Poaceae) in New Zealand, with discussion of its ontogenetic patterns in chaetotaxy - Xu, Yun; Zhang, Fei-Ping; Zhang, Zhi-Qiang (Zootaxa, 2018)
A new species, Prolixus splendens sp. nov., collected from leaves of the grass Austroderia splendens (Poaceae) in Auckland, New Zealand, is described and illustrated. Only five species of Prolixus have previously been reported, and all were recorded from the genus Gahnia (Cyperaceae). In this paper, we present the ontogenetic additions in idiosomal and leg chaetotaxy from larva to adult for the new species. A key to world species of Prolixus is also proposed.